Resident Evil: Object of crime plus Actus Reus - Туляков Вячеслав Олексійович; Туляков Вячеслав Алексеевич; Tulyakov V. A.; Tuliakov, Viacheslav (My University, 2020)
The lecture of course "Criminal Law (General Part)" for students of National University "Odessa Law Academy".
video lecture
Tuliakov V. Resident Evil: Object of crime plus Actus Reus : video lecture / V. Tuliakov. - Odessa, 2020. - Access mode: https://youtu.be/XA46HRCl30g
Keywords: criminal law; crime; object of crime; Actus Reus; уголовное право; кримінальне право